The peroxisome: an update on mysteries - Islinger, Markus; Fahimi, H. Dariush (Histochemistry and cell biology, 2012)
Peroxisomes contribute to several crucial metabolic processes such as β-oxidation of fatty acids, biosynthesis of ether phospholipids and metabolism of reactive oxygen species, which render them indispensable to human health and development. Peroxisomes are highly dynamic organelles that rapidly assemble, multiply and degrade in response to metabolic needs. In recent years, the interest in peroxisomes and their physiological functions has significantly increased. This review intends to highlight recent discoveries and trends in peroxisome research, and represents an update as well as a continuation of a former review article. Novel exciting findings on the biological functions, biogenesis, formation and degradation of peroxisomes, on peroxisomal dynamics and division, as well as on the interaction and cross-talk of peroxisomes with other subcellular compartments are addressed. Furthermore, recent findings on the role of peroxisomes in the brain are discussed.